Distribution of antibiotic resistance genes (ARGs) in anaerobic digestion and land application of swine wastewater. (June 2016) - Sui, Qianwen; Zhang, Junya; Chen, Meixue; Tong, Juan; Wang, Rui; Wei, Yuansong
Abstract: Swine farm and the adjacent farmland are hot spots of ARGs. However, few studies have investigated the on-site occurrence of ARGs distributed in the process of anaerobic digestion (AD) followed by land application of swine wastewater. Two typical swine farms, in southern and northern China respectively, with AD along with land application were explored on ARG distributions. ARGs were highly abundant in raw swine wastewater, AD effectively reduced the copy number of all detected ARGs (0.21–1.34 logs removal), but the relative abundance with different resistance mechanisms showed distinctive variation trends. The reduction efficiency of ARGs was improved by stable operational temperature and longer solid retention time (SRT) of AD. ARGs in soil characterized the contamination from the irrigation of the digested liquor. The total ARGs quantity in soil fell down by 1.66 logs in idle period of winter compared to application period of summer in the northern region, whereas the total amount was steady with whole-year application in south. Some persistent ( sul 1 and sul 2) and elevated ARGs ( tet G and ere A) in AD and land application need more attention. Graphical abstract: Highlights: Swine farm and the adjacent farmland are hot spots of ARGs. Mesophilic anaerobic digestion reduced the most detected ARGs quantities. ARG levels in soils varied with different land application procedures. Persistent and elevated ARGs in AD and land application need more attention. Abstract : Anaerobic digestion reduced the copy number of ARGs in swine wastewater, and winter idle dissipated their quantities in soil.